Soybean and glycine as potential corrosion inhibitors for steel in hydrochloric acid: electrochemical and morphological studies / Solhan Yahya ... [et al.] - Yahya, Solhan; Ahmad, Zuliahani; Che Ismail, Nor Hafizah; Rosli, Nurul Izzati; Ramlan, Nurul Hayani; Radin Sukimi, Nur Aina (Research Management Institute (RMI), 2024)
The potential of soybean and glycine as organic corrosion inhibitors for steel in acid solution was examined through weight loss tests and potentiodynamic polarization. Both soybean and glycine were characterized via FTIR and UV-visible. The result shows that the soybean and glycine contain isoflavone and nitrogen bonds respectively as a beneficial element in inhibiting the corrosion of steel. Corrosion tests were performed with and without the presence of soybean and glycine for 3 days of immersion in the acidic medium. Corrosion inhibition efficiency measured via electrochemical test found that both soybean and glycine give an excellent corrosion inhibition efficiency at 1.5 g/L in 0.5 M HCl up to 96% and 94% respectively. Tafel analysis reveals both inhibitors perform mixed types inhibitors which predominantly anodic inhibition. Pseudo-passivation was observed in the Tafel curve indicating the capabilities of both inhibitors to passivate the corrosion at anodic potential. Observation of the steel samples through an optical microscope shows that the corrosion of the steel surface was inhibited in the addition of soybean and glycine in HCl. The roughness of the steel surface affected by the combination of uniform and pitting corrosion was also reduced. In overall, soybean and glycine exhibit excellent anticorrosive properties due to the presence of significant chemical structures and active functional groups. Analysis of the inhibition mechanism through isotherm showed that soybean and glycine followed Langmuir isotherm, indicating the adsorption type for both inhibitors is chemisorption. The results obtained from this study could be a good reference in diversifying the study of amino acids as metal corrosion inhibitors to benefit metal-based industries.